Neuroendocrine Carcinoma of Urinary Bladder: Extremely a Rare Entity (Bangladesh Journal of Urology, 2020)
Neuroendocrine carcinoma or small cell carcinoma (SCC) of the bladder is a rare and aggressive tumor associated with a poor prognosis. It often presents at a later stage than urothelial carcinoma of the bladder, and comprises less than 1% of bladder malignancies. A number of treatment algorithms have been used to treat bladder SCC, including cystectomy, partial cystectomy, radiotherapy, chemoradiotherapy, chemotherapy alone, and neoadjuvant/adjuvant chemotherapy. Here we are presenting a case of, small cell variety of neuroendocrine carcinoma of the bladder, and its epidemiology, prognosis, and current treatment algorithms are reviewed.Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.166-169